Lithium iron phosphate positive electrode material, preparation method thereof and battery
By bonding the surface of lithium iron phosphate particles to coat carbon nanotubes and using a simplified grinding and drying process, the low compaction density and complex process problems of lithium iron phosphate materials are solved, high conductivity and efficient production are achieved, and battery is improved performance and productivity.
Patent Information
- Application Number
- CN202411538925.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2024-12-31
AI Technical Summary
The existing lithium iron phosphate materials have problems such as low compaction density, complicated preparation process, high energy consumption, poor safety, and long homogenization time when applied to batteries.
The surface of D50 with a spherical or spherical lithium iron phosphate particles is bonded with a binder to coat carbon nanotubes, and the lithium iron phosphate positive electrode material is prepared by grinding and drying, simplifying the process, improving the conductivity and Compress the density and shorten the homogenization time.
The conductive properties and compaction density of lithium iron phosphate materials are significantly improved, the preparation process is simplified, energy consumption is reduced, homogenization time is shortened, production efficiency is improved, and the discharge performance and energy density of the battery are enhanced.
Smart Images

Figure BDA0005112301660000131
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of battery positive electrode materials, and in particular to a lithium iron phosphate positive electrode material and a preparation method thereof and a battery. Background Art
[0002] Lithium iron phosphate materials with olivine structure have very good safety and cycle performance. At the same time, they have the advantages of abundant raw material resources, low price, non-toxicity, environmental friendliness, and good thermal stability. They are widely used in lithium-ion battery energy storage industry and automotive power battery industry. However, due to defects in its crystal structure, lithium iron phosphate materials have poor electronic conductivity and lithium ion migration rate, which limits their development prospects to a certain extent. In view of the shortcomings of lithium iron phosphate, many scholars have also made targeted improvement measures.
[0003] CN111740101B discloses a method for preparing a lithium iron phosphate material, specifically a lithium iron phosphate material with a hollow structure and a preparation method thereof, characterized in that: (1) iron phosphate, a lithium source, a coated carbon source, and a doped ion source are mixed to form a mixed slurry, wherein the coated carbon source is a combination of PEG or soluble starch, PVA, and citric acid; the doped ions are a combination of titanium ions and vanadium ions; (2) the mixed slurry is spray-dried to obtain a precursor; (3) the precursor is sintered to obtain a lithium iron phosphate material. The lithium ion migration speed of the lithium iron phosphate material is increased by mixed doping with metal ions; on the other hand, the conductivity of the lithium iron phosphate material is increased by the combined coated carbon source, and at the same time, the prepared lithium iron phosphate material has a hollow structure, thereby improving its rate performance. However, the lithium iron phosphate material with a hollow structure prepared by this method has a low compaction density, and the material is easily broken during rolling, which destroys the performance of the material, resulting in a narrow practical application of the material.
[0004] CN108199041B discloses a modified lithium iron phosphate material, a preparation method and an application, characterized in that: the modified lithium iron phosphate material is a metal ion doped and carbon-coated lithium iron phosphate material obtained after modification of a metal organic framework and an additional carbon source, wherein the reduction potential of the metal ion is less than -0.27V. The preparation method is to fill the additional carbon source into the pores of MOFs containing a special metal ion M, and then evenly mix it with iron phosphate, a lithium source and a carbon reducing agent, and sinter it under an inert atmosphere to obtain a metal organic framework modified lithium iron phosphate material, that is, a metal ion doped and carbon-coated lithium iron phosphate material. It effectively improves the conductivity of lithium iron phosphate, improves electronic and ionic conductivity, improves its high-rate discharge capability, and is applied to lithium ion battery positive electrode materials. However, the preparation method has cumbersome steps and complex processes, and is not suitable for large-scale production.
[0005] CN102403502B discloses a method for enhancing the conductivity of lithium iron phosphate materials, which is characterized by: using a combination of vapor deposition and mechanical ball milling to wrap low-melting-point metals around lithium iron phosphate material particles. The lithium iron phosphate material modified by this method has lower internal resistance than traditional carbon-coated lithium iron phosphate materials, significantly improved conductivity, and increased tap density. However, the lithium iron phosphate prepared by this method has high energy consumption, and the metals used are mostly highly toxic heavy metals. It is difficult to achieve zero leakage during the production process, which is harmful to the environment and the health of operators, and difficult to achieve industrialization.
[0006] CN105047918A discloses a positive electrode material for a lithium iron phosphate battery, which includes a lithium iron phosphate / carbon nanotube composite, wherein the surface of the lithium iron phosphate / carbon nanotube composite is coated with graphene nanosheets, wherein the mass ratio of lithium iron phosphate to carbon nanotubes in the lithium iron phosphate / carbon nanotube composite is 100:1 to 1:1, and the composite of lithium iron phosphate and carbon nanotubes adopts a granulation process, which improves the tap density of the positive electrode material while ensuring the conductivity of the positive electrode material, and reduces the volume of the conductive carbon material. The use of carbon nanotubes that interact internally to form a conductive network and graphene nanosheets coated on the surface can greatly improve the conductivity of the positive electrode material, improve the power density and charge and discharge speed of the battery, and effectively improve the capacity and cycle performance of the lithium battery. However, when the above-mentioned positive electrode material for a lithium iron phosphate battery is applied to a battery, there may be problems such as unstable bonding of the coating and poor conductivity.
[0007] CN109755488A discloses a high-conductivity nano-lithium iron phosphate battery. The present invention discloses a high-conductivity nano-lithium iron phosphate battery, including a positive electrode slurry, wherein the positive electrode slurry includes lithium iron phosphate, carbon nanotubes and ferrous sulfate. The preparation method of the positive electrode slurry includes the following steps: 1) fully mixing lithium iron phosphate and carbon nanotubes, and high-energy ball milling for 5-24 hours; 2) adding ferrous sulfate to the mixture and stirring for 1-3 hours; 3) allowing the formed slurry to stand for 12-24 hours; 4) obtaining the positive electrode slurry; the present invention adds ferrous sulfate to the positive electrode slurry of the battery, while ensuring a high tap density of iron phosphate, while maintaining a high specific capacity of the product. The above-mentioned positive electrode slurry has the problem that the carbon nanotube dispersion time is long, which makes the positive electrode slurry homogenization time long, which seriously affects the battery production efficiency.
[0008] In summary, the existing lithium iron phosphate materials have the problems of low compaction density, complicated preparation process, high energy consumption in the preparation process, poor safety, and long homogenization time when used in batteries. Summary of the invention
[0009] The first aspect of the present invention is to provide a positive electrode lithium iron phosphate material which can shorten the homogenization time of positive electrode slurry, has good conductivity and stable coating adhesion.
[0010] The second object of the present invention is to provide a method for preparing a lithium iron phosphate material and a battery having high compaction density, simple preparation process, low energy consumption, good safety and the ability to shorten the homogenization time of the positive electrode slurry.
[0011] In a first aspect, the present application provides a lithium iron phosphate positive electrode material, including lithium iron phosphate particles, characterized in that the lithium iron phosphate particles include spherical or quasi-spherical particles with a D50 of 0.5-2 μm, and the surfaces of the lithium iron phosphate particles are coated with carbon nanotubes by a binder.
[0012] In one embodiment, the binder includes at least one of polyvinylidene fluoride, polytetrafluoroethylene and polymethyl methacrylate;
[0013] In one embodiment, the carbon nanotubes include at least one of single-walled carbon nanotubes, multi-walled carbon nanotubes, and lamellar carbon nanotubes;
[0014] In one embodiment, the mass ratio of the lithium iron phosphate particles, the carbon nanotubes and the binder is 83-99.7:0.1-10:0.1-5.
[0015] In one of the embodiments, the mass ratio of the lithium iron phosphate particles, the carbon nanotubes and the binder is 95.5-99.3:0.3-2:0.3-0.5.
[0016] In a second aspect, the present application provides a method for preparing the lithium iron phosphate positive electrode material as described in any of the above embodiments, the preparation method comprising the following steps:
[0017] Mixing carbon nanotube slurry, a binder, a dispersant and a solvent to obtain a carbon nanotube conductive slurry;
[0018] The carbon nanotube conductive slurry and the lithium iron phosphate material are mixed and ground to make the carbon nanotubes evenly dispersed on the surface of the lithium iron phosphate material to obtain a mixed slurry;
[0019] The mixed slurry is dried to obtain a lithium iron phosphate positive electrode material.
[0020] In one of the embodiments, the carbon nanotube slurry includes at least one of single-walled carbon nanotube slurry, multi-walled carbon nanotube slurry, and lamellar carbon nanotube slurry;
[0021] In one embodiment, the binder includes at least one of polyvinylidene fluoride, polytetrafluoroethylene and polymethyl methacrylate;
[0022] In one embodiment, the dispersant includes at least one of hydrogenated nitrile rubber and polyvinyl pyrrolidone;
[0023] In one embodiment, the solvent includes N-methylpyrrolidone, and the solid content of the carbon nanotube conductive paste is 2-5%.
[0024] In one embodiment, taking the total solid mass of the lithium iron phosphate, carbon nanotubes, dispersant and binder as 100%, the amount of the carbon nanotubes added is 0.1%-10%; and / or the amount of the binder added is 0.1%-5%; and / or the amount of the dispersant added is 0.1%-2%.
[0025] In one embodiment, the amount of the carbon nanotubes added is 0.3%-2%, and / or the amount of the binder added is 0.3%-0.5%.
[0026] In one embodiment, the grinding process is performed using a grinder for a grinding time of 0.5-10 h, preferably 0.5-2 h.
[0027] In one embodiment, the drying method includes any one of freeze drying, spray drying, vacuum drying, forced air drying, and vacuum rotary drying; preferably, spray drying; preferably, the atomizing gas pressure of the spray drying is 0.01MPa-0.35MPa.
[0028] In one embodiment, the drying is performed under a protective atmosphere, and the protective gas includes at least one of helium, argon or nitrogen, preferably nitrogen.
[0029] In a third aspect, the present application provides a lithium battery, wherein the positive electrode sheet of the lithium battery comprises the lithium iron phosphate positive electrode material as described in any of the above embodiments; or, the positive electrode sheet of the lithium battery comprises the lithium iron phosphate positive electrode material prepared by the method described in any of the above embodiments.
[0030] In a fourth aspect, the present application provides the use of lithium batteries in electronic equipment, transportation equipment, energy storage equipment or automobiles.
[0031] The above-mentioned lithium iron phosphate positive electrode material includes lithium iron phosphate particles, and the lithium iron phosphate particles include spherical or quasi-spherical particles with a D50 of 0.5-2μm, and the surface of the lithium iron phosphate particles is coated with carbon nanotubes by a binder. Because the surface of the lithium iron phosphate material is evenly coated with carbon nanotubes, carbon nanotubes do not need to be added in the subsequent homogenization process of the positive electrode slurry, which not only avoids the phenomenon of uneven dispersion of the conductive agent, but also shortens the process time of the homogenization, improves production efficiency, and has very significant economic benefits. In this application, carbon nanotubes are bonded and coated on the surface of spherical or quasi-spherical lithium iron phosphate particles with a D50 of 0.5-2μm by a binder. The nanotubes have good bonding strength and can significantly improve the conductive properties of the material. It also has the advantages of good conductive properties and high compaction density. The coating has stable bonding and good conductivity. In particular, the present application adopts spherical or quasi-spherical lithium iron phosphate particles with a D50 of 0.5-2μm. On the one hand, it can better ensure that the carbon nanotubes are dispersed and evenly distributed on the surface of the lithium iron phosphate particles during the preparation process, which can significantly improve the conductivity of the lithium iron phosphate positive electrode material and improve the subsequent discharge performance and discharge capacity. On the other hand, spherical or quasi-spherical lithium iron phosphate particles with a D50 of 0.5-2μm have a higher specific surface area, which helps to improve the utilization rate of active materials and the energy density of the battery.
[0032] Moreover, the preparation process of the lithium iron phosphate positive electrode material of the present application is simple. The present invention mixes the lithium iron phosphate with the carbon nanotube conductive slurry by grinding and other methods, and dries it. After drying, it does not need to be sintered again to obtain a highly conductive lithium iron phosphate material, which saves energy consumption and greatly improves the conductivity of the lithium iron phosphate material. The method of the present invention is simple and easy to realize large-scale industrialization. There is no special requirement for the lithium iron phosphate material and it has a wide range of applications. And because the surface of the lithium iron phosphate material is evenly coated with carbon nanotubes, carbon nanotubes do not need to be added during the homogenization process, which not only avoids the phenomenon of uneven dispersion of the conductive agent, but also shortens the homogenization process time, improves production efficiency, and has very significant economic benefits.
[0033] The present invention mixes lithium iron phosphate and carbon nanotubes by grinding and other methods, and dries them by spray drying and other methods. After drying, no re-sintering is required, which saves energy consumption and greatly improves the conductivity of lithium iron phosphate materials. The method of the present invention is simple and easy to realize large-scale industrialization. It has no special requirements for lithium iron phosphate materials and does not affect the compaction and other processing properties of lithium iron phosphate materials. It has a wide range of applications. Because the surface of the lithium iron phosphate material is evenly coated with carbon nanotubes, carbon nanotubes do not need to be added during the homogenization process, which not only avoids the phenomenon of uneven dispersion of the conductive agent, but also shortens the process time of the homogenization, improves production efficiency, and has very significant economic benefits. DETAILED DESCRIPTION
[0034] In order to facilitate the understanding of the present application, in order to make the above-mentioned purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are described in detail below. In the following description, many specific details are set forth to facilitate a full understanding of the present application, and a preferred implementation method of the present application is given. However, the present application can be implemented in many different forms and is not limited to the implementation methods described herein. On the contrary, the purpose of providing these implementation methods is to make the disclosure of the present application more thoroughly and comprehensively understood. The present application can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present application, so the present application is not limited by the specific embodiments disclosed below. In addition, the terms "first" and "second" are only used for descriptive purposes, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Thus, the features defined as "first" and "second" can explicitly or implicitly include at least one of the features. In the description of the present application, the meaning of "multiple" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined. In the description of the present application, the meaning of "several" is at least one, such as one, two, etc., unless otherwise clearly and specifically defined. An element is considered to be "connected" to another element, which may be directly connected to another element or may have a centered element at the same time. The terms "vertical", "horizontal", "left", "right" and similar expressions used herein are for illustrative purposes only and are not intended to be the only implementation method. Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein are only for the purpose of describing specific implementation methods and are not intended to limit this application. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0035] In a first aspect, the present application provides a lithium iron phosphate positive electrode material, including lithium iron phosphate particles, characterized in that the lithium iron phosphate particles are spherical or quasi-spherical particles with a D50 of 0.5-2 μm, and the surfaces of the lithium iron phosphate particles are coated with carbon nanotubes by a binder.
[0036] The above-mentioned lithium iron phosphate positive electrode material includes lithium iron phosphate particles, and the lithium iron phosphate particles are spherical or quasi-spherical particles with a D50 of 0.5-2μm, and the surface of the lithium iron phosphate particles is coated with carbon nanotubes by a binder. Because the surface of the lithium iron phosphate material is evenly coated with carbon nanotubes, carbon nanotubes do not need to be added in the subsequent homogenization process of the positive electrode slurry, which not only avoids the phenomenon of uneven dispersion of the conductive agent, but also shortens the process time of the homogenization, improves production efficiency, and has very significant economic benefits. In this application, carbon nanotubes are bonded and coated on the surface of spherical or quasi-spherical lithium iron phosphate particles with a D50 of 0.5-2μm by a binder. The nanotubes have good bonding strength, can significantly improve the conductive properties of the material, and also have the advantages of good conductive properties and high compaction density. In particular, the present application adopts spherical or quasi-spherical lithium iron phosphate particles with a D50 of 0.5-2μm. On the one hand, it can better ensure that the carbon nanotubes are dispersed and evenly distributed on the surface of the lithium iron phosphate particles during the preparation process, which can significantly improve the conductivity of the lithium iron phosphate positive electrode material and improve the subsequent discharge performance and discharge capacity. On the other hand, spherical or quasi-spherical lithium iron phosphate particles with a D50 of 0.5-2μm have a higher specific surface area, which helps to improve the utilization rate of active materials and the energy density of the battery.
[0037] In one embodiment, the binder includes at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE) and polymethyl methacrylate (PMMA); thus, by using the above binder, the carbon nanotubes and lithium iron phosphate can be better combined more closely, reducing the movement and deformation of the material, thereby increasing the energy density of the battery and reducing the internal resistance. These improvements help to improve the overall performance and efficiency of the battery, especially significantly improving the conductivity of the material.
[0038] In one embodiment, the carbon nanotubes include at least one of single-walled carbon nanotubes, multi-walled carbon nanotubes, and lamellar carbon nanotubes; thus, by using the above carbon nanotubes, the conductivity of the positive electrode material used in the battery can be improved, the battery cycle life can be enhanced, and the battery energy density and charge and discharge performance can be improved. In addition, the carbon nanotubes have a stable structure and are not prone to safety issues such as thermal runaway, which can also improve the safety of the battery.
[0039] In one embodiment, the mass ratio of the lithium iron phosphate particles, the carbon nanotubes and the binder is 83-99.7: 0.1-10: 0.1-5. Preferably, the mass ratio of the lithium iron phosphate particles, the carbon nanotubes and the binder is 95.5-99.3: 0.3-2: 0.3-0.5. In this way, by using the lithium iron phosphate positive electrode material of the above mass ratio of lithium iron phosphate particles, the carbon nanotubes and the binder, the conductivity is good, which can improve the conductivity of the positive electrode material when it is subsequently applied to the battery, enhance the battery cycle life, and improve the battery energy density and charge and discharge performance. Moreover, the structure of the carbon nanotubes is stable, and it is not easy to have safety problems such as thermal runaway, which can also improve the safety of the battery. Preferably, the mass ratio of the lithium iron phosphate particles, the carbon nanotubes and the binder is 98.5: 1: 0.4.
[0040] In a second aspect, the present application provides a method for preparing the lithium iron phosphate positive electrode material as described in any of the above embodiments, the preparation method comprising the following steps s1 to s3:
[0041] S1: mixing carbon nanotube slurry, a binder, a dispersant and a solvent to obtain a carbon nanotube conductive slurry;
[0042] For example, the carbon nanotube slurry includes at least one of single-walled carbon nanotube slurry, multi-walled carbon nanotube slurry, and lamellar carbon nanotube slurry; for example, the binder includes at least one of polyvinylidene fluoride, polytetrafluoroethylene, and polymethyl methacrylate; for example, the dispersant includes at least one of hydrogenated nitrile rubber and polyvinyl pyrrolidone; for example, the solvent includes N-methylpyrrolidone, and the solid content of the carbon nanotube conductive slurry is 2-5%. For example, taking the total solid mass of the lithium iron phosphate, carbon nanotubes, dispersant, and binder as 100%, the amount of the carbon nanotube added is 0.1%-10%, preferably 0.3%-2%; the amount of the binder added is 0.1%-5%, preferably 0.3%-0.5%; the amount of the dispersant added is 0.1%-2%. For example, the mass ratio of the lithium iron phosphate particles, the carbon nanotubes, the binder and the dispersant is 95.5-99.3: 0.3-2: 0.3-0.5: 0.1-2. Preferably, the mass ratio of the lithium iron phosphate particles, the carbon nanotubes, the binder and the dispersant is 98.5: 1: 0.4: 0.1.
[0043] S2: mixing the carbon nanotube conductive slurry and the lithium iron phosphate material and grinding them so that the carbon nanotubes are evenly dispersed on the surface of the lithium iron phosphate material to obtain a mixed slurry;
[0044] For example, a grinder is used for grinding during the grinding process, and the grinding time is 0.5-10 hours, preferably 0.5-2 hours. In this way, the lithium iron phosphate and the carbon nanotubes can be well mixed by grinding and other methods.
[0045] S3: Drying the mixed slurry to obtain a lithium iron phosphate positive electrode material.
[0046] For example, the drying method includes any one of freeze drying, spray drying, vacuum drying, blast drying, and vacuum rotary drying; preferably, spray drying; preferably, the atomizing gas pressure of the spray drying is 0.01MPa-0.35MPa. In this way, the spray drying method has the advantages of rapid dissolution and convenient dispersion.
[0047] For example, the drying is performed under a protective atmosphere, and the protective gas includes at least one of helium, argon or nitrogen, preferably nitrogen. In this way, drying under the protection of a protective atmosphere is beneficial to reducing or eliminating moisture and improving battery safety performance.
[0048] The lithium iron phosphate positive electrode material preparation process of the present application is simple. The present invention mixes lithium iron phosphate and carbon nanotube conductive slurry by grinding and other methods, and dries them. After drying, no re-sintering is required to obtain a highly conductive lithium iron phosphate material, which saves energy consumption and greatly improves the conductivity of the lithium iron phosphate material. The method of the present invention is simple and easy to realize large-scale industrialization. There is no special requirement for lithium iron phosphate materials and it has a wide range of applications. And because the surface of the lithium iron phosphate material is evenly coated with carbon nanotubes, carbon nanotubes do not need to be added during the homogenization process, which not only avoids the phenomenon of uneven dispersion of the conductive agent, but also shortens the homogenization process time, improves production efficiency, and has very significant economic benefits.
[0049] The present invention mixes lithium iron phosphate and carbon nanotubes by grinding and other methods, and dries them by spray drying and other methods. After drying, no re-sintering is required, which saves energy consumption and greatly improves the conductivity of lithium iron phosphate materials. The method of the present invention is simple and easy to realize large-scale industrialization. It has no special requirements for lithium iron phosphate materials and does not affect the compaction and other processing properties of lithium iron phosphate materials. It has a wide range of applications. Because the surface of the lithium iron phosphate material is evenly coated with carbon nanotubes, carbon nanotubes do not need to be added during the homogenization process, which not only avoids the phenomenon of uneven dispersion of the conductive agent, but also shortens the process time of the homogenization, improves production efficiency, and has very significant economic benefits.
[0050] In a third aspect, the present application provides a lithium battery, wherein the positive electrode sheet of the lithium battery comprises the lithium iron phosphate positive electrode material as described in any of the above embodiments; or, the positive electrode sheet of the lithium battery comprises the lithium iron phosphate positive electrode material prepared by the method described in any of the above embodiments.
[0051] The lithium battery of the present application adopts the above-mentioned lithium iron phosphate positive electrode material, including lithium iron phosphate particles, the lithium iron phosphate particles are spherical or quasi-spherical particles with a D50 of 0.5-2μm, and the surface of the lithium iron phosphate particles is coated with carbon nanotubes by a binder. Because the surface of the lithium iron phosphate material is evenly coated with carbon nanotubes, carbon nanotubes do not need to be added in the subsequent homogenization process of the positive electrode slurry, which not only avoids the phenomenon of uneven dispersion of the conductive agent, but also shortens the process time of the homogenization, improves production efficiency, and has very significant economic benefits. The present application uses a binder to bond and coat carbon nanotubes on the surface of spherical or quasi-spherical lithium iron phosphate particles with a D50 of 0.5-2μm. The nanotubes have good bonding strength and can significantly improve the conductive properties of the material. It also has the advantages of good conductive properties and high compaction density. In particular, the present application adopts spherical or quasi-spherical lithium iron phosphate particles with a D50 of 0.5-2μm. On the one hand, it can better ensure that the carbon nanotubes are dispersed and evenly distributed on the surface of the lithium iron phosphate particles during the preparation process, which can significantly improve the conductivity of the lithium iron phosphate positive electrode material and improve the subsequent discharge performance and discharge capacity. On the other hand, spherical or quasi-spherical lithium iron phosphate particles with a D50 of 0.5-2μm have a higher specific surface area, which helps to improve the utilization rate of active materials and the energy density of the battery.
[0052] In one embodiment, the positive electrode sheet of a lithium battery includes a current collector and an active layer located on the current collector, wherein the active layer includes a lithium iron phosphate positive electrode material, a conductive agent (acetylene black (SP)), and a binder (PVDF (HSV-5130)), wherein the mass ratio of the lithium iron phosphate positive electrode material, the conductive agent, and the binder is 9.5:0.3:0.2. For another example, NMP solvent is added during the preparation of the active layer. For another example, the current collector is an aluminum foil having a thickness of 16 μm, and is not limited thereto. For another example, the preparation method of the active layer is as follows: weigh a lithium iron phosphate positive electrode material as the positive electrode material, add acetylene black (SP) as a conductive agent and PVDF (HSV-5130) as a binder, mix thoroughly, add NMP to a solid content of 70% for dispersion, and obtain a positive electrode slurry after homogenization, and draw the slurry on the aluminum foil to form a positive electrode sheet.
[0053] In the fourth aspect, the present application provides the use of lithium batteries in electronic equipment, transportation equipment, energy storage equipment or automobiles. For example, electronic equipment includes but is not limited to mobile phones, tablets, wearable devices, etc.; transportation equipment includes ships, cars, aircraft such as drones, etc., and energy storage equipment includes home storage equipment, variable storage, power station energy storage, etc.
[0054] The present application will be further described below in conjunction with specific embodiments and comparative examples.
[0055] Example 1
[0056] The preparation method of the lithium iron phosphate positive electrode material provided in this embodiment includes:
[0057] (1) mixing single-walled carbon nanotube slurry, a binder (PVDF), a dispersant (H-NBR) and a solvent (NMP) to obtain a carbon nanotube conductive slurry;
[0058] (2) grinding the carbon nanotube conductive slurry and the lithium iron phosphate material with a grinder for 1.5 hours to uniformly disperse the carbon nanotubes on the surface of the lithium iron phosphate material to obtain a mixed slurry;
[0059] (3) spray drying the mixed slurry under nitrogen conditions with an atomizing gas pressure of 0.2 MPa to obtain a lithium iron phosphate positive electrode material. The solid content of the carbon nanotube conductive slurry is 3%, and the mass ratio of the lithium iron phosphate, single-walled carbon nanotube, binder, and dispersant is 98.5:1:0.4:0.1.
[0060] Example 2
[0061] The lithium iron phosphate positive electrode material and the preparation method thereof are different from those of Example 1 only in that, in the preparation method of the lithium iron phosphate positive electrode material, the mass ratio of lithium iron phosphate, single-walled carbon nanotubes, binder and dispersant is 95.5:2:0.5:2.
[0062] Example 3
[0063] The lithium iron phosphate positive electrode material and the preparation method thereof are different from those of Example 1 only in that, in the preparation method of the lithium iron phosphate positive electrode material, the mass ratio of lithium iron phosphate, single-walled carbon nanotubes, binder and dispersant is 99.3:0.3:0.3:0.1.
[0064] Example 4
[0065] The lithium iron phosphate positive electrode material and the preparation method thereof are different from those of Example 1 only in that the grinding time of the grinder in step (2) is 2 hours.
[0066] Example 5
[0067] The lithium iron phosphate positive electrode material and the preparation method thereof are different from those of Example 1 only in that the grinding time of the grinder in step (2) is 0.5 h.
[0068] Example 6
[0069] The lithium iron phosphate positive electrode material and the preparation method thereof are different from those of Example 1 only in that the atomization pressure of the spray drying in step (3) is 0.35 MPa.
[0070] Example 7
[0071] The lithium iron phosphate positive electrode material and the preparation method thereof are different from those of Example 1 only in that the atomizing gas pressure of the spray drying in step (3) is 0.01 MPa.
[0072] Comparative Example 1
[0073] The lithium iron phosphate positive electrode material and the preparation method thereof are different from those of Example 1 only in that no dispersant is added during the lithium iron phosphate positive electrode material and the preparation process thereof.
[0074] Comparative Example 2
[0075] The lithium iron phosphate positive electrode material and the preparation method thereof are different from those of Example 1 only in that no binder is added during the lithium iron phosphate positive electrode material and the preparation process thereof.
[0076] Application Example 1
[0077] A secondary lithium-ion battery comprises a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte.
[0078] The method for preparing a secondary lithium-ion battery provided in this application example comprises the following steps:
[0079] 9.5 g of lithium iron phosphate positive electrode material (Example 1) was weighed as the positive electrode material, 0.3 g of acetylene black (SP) was added as a conductive agent, and 0.2 g of PVDF (HSV-5130) was added as a binder. After fully mixing, NMP was added to a solid content of 70% for dispersion. After homogenization, a positive electrode slurry was obtained, and the slurry was drawn on a 16 μm thick aluminum foil to form a positive electrode sheet.
[0080] The metal lithium sheet is used as the negative electrode.
[0081] The diaphragm is a ceramic diaphragm, which includes a base film with a thickness of 12 μm and a ceramic coating with a thickness of 4 μm on both sides of the base film.
[0082] The composition of the electrolyte is as follows: ethylene carbonate (EC) and propylene carbonate (PC) in a volume ratio of 1:1, and the concentration of LiPF6 is 1 mol / L.
[0083] In an anaerobic glove box, the positive electrode sheet, negative electrode sheet, separator and electrolyte were used to assemble a CR2032 button cell.
[0084] Application Example 2-7
[0085] A secondary lithium-ion battery, which differs from Application Example 1 in that the lithium iron phosphate positive electrode material of Example 1 is replaced by the lithium iron phosphate positive electrode material of Examples 2-8 respectively.
[0086] Application Comparative Example 1-2
[0087] A secondary lithium-ion battery, which differs from Application Example 1 in that the lithium iron phosphate positive electrode material of Example 1 is replaced by the lithium iron phosphate positive electrode material of Comparative Examples 1-2 respectively.
[0088] Application Comparative Example 3
[0089] A secondary lithium ion battery is different from Application Example 1 in that the lithium iron phosphate positive electrode material of Example 1 is replaced by an initial lithium iron phosphate positive electrode material that has not been modified with carbon nanotubes.
[0090] Performance Test:
[0091] (1) First discharge capacity test: In the voltage range of 2.5-3.65V, the test temperature is 25℃, and the 0.1C discharge capacity is measured at a rate of 0.1C.
[0092] (2) Rate performance test: Within the voltage range of 2.5-3.65V and the test temperature of 25°C, the discharge capacity was measured at 1C and 5C respectively. The discharge capacity at 1C is C1, and the discharge capacity at 5C is C2. The rate performance of 5C / 1C (%) = C2 / C1×100%.
[0093] (3) Cycle performance test: within the voltage range of 2.5-3.65V, the test temperature is 25°C, 1C charge and discharge cycle is 200 cycles, the first discharge capacity is C0, the 200th cycle discharge capacity is C3, 1C cycle capacity retention rate (%) = C3 / C0×100%.
[0094] The secondary lithium-ion batteries provided in Examples 1 to 7 and Comparative Application Examples 1 to 3 were tested according to the above test method. The test results are shown in Table 1:
[0095] Table 1 Test results of various application examples and comparative examples
[0096]
[0097] Note: The test results of the above embodiments and comparative examples are all the test results of the above application embodiments and comparative examples.
[0098] As can be seen from the above, Application Example 1 uses the lithium iron phosphate positive electrode material of Example 1, which has higher capacity and rate performance than other embodiments and comparative examples, and the cyclicity is relatively high. When the grinding time is extended from 1.5h to 2.0h compared with Example 1, the relevant performance is not improved in Example 4, and the surface grinding time of 1.5h is more suitable. When the grinding time is reduced to 0.5h in Example 5, the gram capacity, rate performance and cycle performance are relatively reduced. By comparing Example 1 with Examples 6-7, it can be seen that when the atomizing pressure increases or decreases during drying, the gram capacity, rate performance and cycle performance are all reduced, indicating that the atomizing pressure of nitrogen during drying is 0.2MPa. It is more suitable. When no dispersant and binder are used in Comparative Examples 1 and Comparative Examples 2, the gram capacity, rate performance and cycle performance are all reduced, and Comparative Example 3 uses conventional lithium iron phosphate materials (that is, carbon nanotubes are not used for coating) The gram capacity, rate performance and cycle performance are all relatively the lowest. It can be seen that the lithium iron phosphate positive electrode material provided by the present application can significantly improve the gram capacity, rate performance and cycle performance of the battery. In particular, the use of the lithium iron phosphate positive electrode material of the present application can significantly reduce the subsequent homogenization time of the positive electrode slurry, can significantly improve the battery manufacturing process, and increase the unit output of the manufacturing unit.
[0099] The above-mentioned lithium iron phosphate positive electrode material includes lithium iron phosphate particles, and the lithium iron phosphate particles include spherical or quasi-spherical particles with a D50 of 0.5-2μm, and the surface of the lithium iron phosphate particles is coated with carbon nanotubes by a binder. Because the surface of the lithium iron phosphate material is evenly coated with carbon nanotubes, carbon nanotubes do not need to be added in the subsequent homogenization process of the positive electrode slurry, which not only avoids the phenomenon of uneven dispersion of the conductive agent, but also shortens the process time of the homogenization, improves production efficiency, and has very significant economic benefits. In this application, carbon nanotubes are bonded and coated on the surface of spherical or quasi-spherical lithium iron phosphate particles with a D50 of 0.5-2μm by a binder. The nanotubes have good bonding strength and can significantly improve the conductive properties of the material. It also has the advantages of good conductive properties and high compaction density. The coating has stable bonding and good conductivity. In particular, the present application adopts spherical or quasi-spherical lithium iron phosphate particles with a D50 of 0.5-2μm. On the one hand, it can better ensure that the carbon nanotubes are dispersed and evenly distributed on the surface of the lithium iron phosphate particles during the preparation process, which can significantly improve the conductivity of the lithium iron phosphate positive electrode material and improve the subsequent discharge performance and discharge capacity. On the other hand, spherical or quasi-spherical lithium iron phosphate particles with a D50 of 0.5-2μm have a higher specific surface area, which helps to improve the utilization rate of active materials and the energy density of the battery.
[0100] Moreover, the preparation process of the lithium iron phosphate positive electrode material of the present application is simple. The present invention mixes the lithium iron phosphate with the carbon nanotube conductive slurry by grinding and other methods, and dries it. After drying, it does not need to be sintered again to obtain a highly conductive lithium iron phosphate material, which saves energy consumption and greatly improves the conductivity of the lithium iron phosphate material. The method of the present invention is simple and easy to realize large-scale industrialization. There is no special requirement for the lithium iron phosphate material and it has a wide range of applications. And because the surface of the lithium iron phosphate material is evenly coated with carbon nanotubes, carbon nanotubes do not need to be added during the homogenization process, which not only avoids the phenomenon of uneven dispersion of the conductive agent, but also shortens the homogenization process time, improves production efficiency, and has very significant economic benefits.
[0101] The present invention mixes lithium iron phosphate and carbon nanotubes by grinding and other methods, and dries them by spray drying and other methods. After drying, no re-sintering is required, which saves energy consumption and greatly improves the conductivity of lithium iron phosphate materials. The method of the present invention is simple and easy to realize large-scale industrialization. It has no special requirements for lithium iron phosphate materials and does not affect the compaction and other processing properties of lithium iron phosphate materials. It has a wide range of applications. Because the surface of the lithium iron phosphate material is evenly coated with carbon nanotubes, carbon nanotubes do not need to be added during the homogenization process, which not only avoids the phenomenon of uneven dispersion of the conductive agent, but also shortens the process time of the homogenization, improves production efficiency, and has very significant economic benefits.
[0102] The technical features of the above-described embodiments can be combined arbitrarily. In order to make the description concise, all possible combinations of the technical features in the above-described embodiments are not described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification. It should be noted that "in one embodiment", "for example", "for example", etc. in this application are intended to illustrate the present application, rather than to limit the present application. The above-described embodiments only express several implementation methods of the present application, and the description is relatively specific and detailed, but it cannot be understood as a limitation on the scope of the patent application. It should be pointed out that for a person of ordinary skill in the art, without departing from the concept of the present application, several variations and improvements can also be made, which all belong to the scope of protection of the present application. Therefore, the scope of protection of the patent in this application shall be subject to the attached claims.
Claims
1. A lithium iron phosphate positive electrode material, comprising lithium iron phosphate particles, characterized in that: Lithium iron phosphate particles include D 50 The particles are spherical or quasi-spherical particles with a diameter of 0.5-2 μm, and the surfaces of the lithium iron phosphate particles are coated with carbon nanotubes by bonding with a binder.
2. The lithium iron phosphate positive electrode material according to claim 1, characterized in that: The binder comprises at least one of polyvinylidene fluoride, polytetrafluoroethylene and polymethyl methacrylate; And / or, the carbon nanotubes include at least one of single-walled carbon nanotubes, multi-walled carbon nanotubes, and lamellar carbon nanotubes; And / or, the mass ratio of the lithium iron phosphate particles, the carbon nanotubes and the binder is 83-99.7:0.1-10:0.1-5.
3. The lithium iron phosphate positive electrode material according to claim 2, characterized in that: The mass ratio of the lithium iron phosphate particles, the carbon nanotubes and the binder is 95.5-99.3:0.3-2:0.3-0.
5.
4. A method for preparing a lithium iron phosphate positive electrode material as claimed in any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: Mixing carbon nanotube slurry, a binder, a dispersant and a solvent to obtain a carbon nanotube conductive slurry; The carbon nanotube conductive slurry and the lithium iron phosphate material are mixed and ground to make the carbon nanotubes evenly dispersed on the surface of the lithium iron phosphate material to obtain a mixed slurry; The mixed slurry is dried to obtain a lithium iron phosphate positive electrode material.
5. The preparation method according to claim 4, characterized in that: The carbon nanotube slurry includes at least one of single-walled carbon nanotube slurry, multi-walled carbon nanotube slurry, and lamellar carbon nanotube slurry; And / or, the binder includes at least one of polyvinylidene fluoride, polytetrafluoroethylene and polymethyl methacrylate; and / or, the dispersant comprises at least one of hydrogenated nitrile rubber and polyvinyl pyrrolidone; And / or, the solvent includes N-methylpyrrolidone, and the solid content of the carbon nanotube conductive paste is 2-5%.
6. The preparation method according to claim 4, characterized in that: Taking the total solid mass of the lithium iron phosphate, carbon nanotubes, dispersant and binder as 100%, the added amount of the carbon nanotubes is 0.1%-10%; and / or the added amount of the binder is 0.1%-5%; and / or the added amount of the dispersant is 0.1%-2%.
7. The preparation method according to claim 6, characterized in that: The amount of the carbon nanotubes added is 0.3%-2%, and / or the amount of the binder added is 0.3%-0.5%.
8. The preparation method according to claim 4, characterized in that: The grinding process is performed using a grinder for a grinding time of 0.5-10 h, preferably 0.5-2 h; And / or, the drying method includes any one of freeze drying, spray drying, vacuum drying, blast drying, and vacuum rotary drying; preferably, spray drying; preferably, the atomizing gas pressure of the spray drying is 0.01MPa-0.35MPa; And / or, the drying is performed under a protective atmosphere, wherein the protective gas comprises at least one of helium, argon or nitrogen, preferably nitrogen.
9. A lithium battery, characterized in that: The positive electrode sheet of the lithium battery contains the lithium iron phosphate positive electrode material as described in any one of claims 1 to 3; or, the positive electrode sheet of the lithium battery contains the lithium iron phosphate positive electrode material prepared by the method as described in any one of claims 4 to 8.
10. Use of the lithium battery as claimed in claim 9 in electronic equipment, transportation equipment, energy storage equipment or automobiles.
Citation Information
Cited By
Preparation method of lithium iron phosphate positive electrode material
CN121247761A
